2008
DOI: 10.1098/rsbl.2008.0454
|View full text |Cite
|
Sign up to set email alerts
|

A threat to coral reefs multiplied? Four species of crown-of-thorns starfish

Abstract: In the face of ever-increasing threats to coral reef ecosystems, it is essential to understand the impact of natural predators in order to devise appropriate management strategies. Destructive population explosions of the crown-of-thorns starfish Acanthaster planci have devastated coral reefs throughout the Indo-Pacific for decades. But despite extensive research, the causes of outbreaks are still unclear. An important consideration in this research is that A. planci has been regarded as a single taxonomic ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
151
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 23 publications
9
151
1
2
Order By: Relevance
“…While these patterns are clear in some species (e.g., Barber et al 2002, DeBoer et al 2008, 2014b, they can be less clear in others. For example, Vogler et al (2008) demonstrated that the crown of thorns sea star, Acanthaster planci (Linnaeus, 1758), is likely a species complex and multiple "species" and haplogroups are distributed across the Coral Triangle. However, it is unclear whether overlapping distributions in the Coral Triangle result from secondary contact (with potential hybridization) following allopatric speciation, or whether speciation resulted from natural selection in sympatry.…”
Section: Origins Of Marinementioning
confidence: 99%
“…While these patterns are clear in some species (e.g., Barber et al 2002, DeBoer et al 2008, 2014b, they can be less clear in others. For example, Vogler et al (2008) demonstrated that the crown of thorns sea star, Acanthaster planci (Linnaeus, 1758), is likely a species complex and multiple "species" and haplogroups are distributed across the Coral Triangle. However, it is unclear whether overlapping distributions in the Coral Triangle result from secondary contact (with potential hybridization) following allopatric speciation, or whether speciation resulted from natural selection in sympatry.…”
Section: Origins Of Marinementioning
confidence: 99%
“…Wilson et al 2007;Raupach et al 2007Raupach et al , 2009Vogler et al 2008). On the contrary, genetic analyses have also revealed the existence of truly cosmopolitan species in some planktotrophic taxa (Meyer et al 2008) and also peracarid brooders (C. Held pers.…”
Section: Cryptic Speciesmentioning
confidence: 99%
“…Molecular work on the starfish A. planci, including specimens from Panama, revealed that it is not in fact a single species, but a pan-Indo-Pacific species complex consisting of four deeply diverged clades (Pacific, Red Sea, Northern Indian Ocean, and Southern Indian Ocean) (Vogler et al 2008). These clades reportedly diverged between 1.95 and 3.65 mya (Pliocene to early Pleistocene) and have genetic distances (8.8-10.6 %) equivalent to the distances between other sibling species of starfish (Waters et al 2004).…”
Section: Evolutionmentioning
confidence: 99%
“…These clades reportedly diverged between 1.95 and 3.65 mya (Pliocene to early Pleistocene) and have genetic distances (8.8-10.6 %) equivalent to the distances between other sibling species of starfish (Waters et al 2004). Vogler et al (2008) propose that this speciation process was driven by sea level changes (Pillans et al 1998) that isolated populations.…”
Section: Evolutionmentioning
confidence: 99%